1983
DOI: 10.1007/bf00182956
|View full text |Cite
|
Sign up to set email alerts
|

Evoked potentials in rats with misonidazole neurotoxicity

Abstract: Central neurotoxicity produced in rats by daily administration of 300 mg/kg of misonidazole (MISO) 5 times/week for 4-5 weeks (total dose = 6.0 gm/kg) was evaluated weekly wit brain stem auditory evoked potentials (BAEPs). Compared to untreated control rats, all treated rats had a prolongation of the I-IV interpeak latency (p less than 0.005) at a mean of 13.2 +/- 2.7 days at a cumulative dose of approximately 4.0 gm/kg of MISO per rat. In some rats, the I-III and I-II interwave latencies were prolonged and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…1~ Table 1). Rats in this study tolerated significantly higher total doses of MISO than rats in the previous study (4). Clinical signs of toxicity began to appear at approximately the time of the 33rd injection (X = 4.455 g MISO) (Fig.…”
Section: Latencymentioning
confidence: 54%
See 1 more Smart Citation
“…1~ Table 1). Rats in this study tolerated significantly higher total doses of MISO than rats in the previous study (4). Clinical signs of toxicity began to appear at approximately the time of the 33rd injection (X = 4.455 g MISO) (Fig.…”
Section: Latencymentioning
confidence: 54%
“…Recordings were performed as described (4). Potentials were amplified by a gain of 10,000 with bandpass filtration of 30 HZ-3 KHz for BAEP recordings and 5 100 Hz for CEP recordings.…”
Section: Recording Of Baep and Cepmentioning
confidence: 99%
“…In rats, it has been shown that following exposure to misonidazole neurotoxicity, Peaks I and I1 were the only peaks not affected (17). In the same study, histologic examination showed consistent necrosis in the cochlear nuclei, leading the authors to suggest that the generator for Peak I1 is the auditory nerve.…”
Section: Discussionmentioning
confidence: 87%
“…Although the generator site for Peak I1 was once thought to be the cochlear nucleus, more recent evidence suggests that it is the auditory nerve ( 17,18). In rats, it has been shown that following exposure to misonidazole neurotoxicity, Peaks I and I1 were the only peaks not affected (17).…”
Section: Discussionmentioning
confidence: 97%
“…In independent studies, Rebert and ourselves have shown that the brain stem conduction time of the BAEP (wave I to wave IV interpeak latency) is prolonged after chronic administration of MISO (1,5). This is expected, because lesions involving the cochlear and vestibular nuclei and other periventricular brain stem nuclei brain are typically produced in rats by MISO.…”
Section: Discussionmentioning
confidence: 93%